Mouse Mammary Tumour Virus (MMTV) in Human Breast Cancer—The Value of Bradford Hill Criteria - James S. Lawson; Wendy K. Glenn (Viruses, 2022)
For many decades, the betaretrovirus, mouse mammary tumour virus (MMTV), has been a causal suspect for human breast cancer. In recent years, substantial new evidence has been developed. Based on this evidence, we hypothesise that MMTV has a causal role. We have used an extended version of the classic A. Bradford Hill causal criteria to assess the evidence. 1. Identification of MMTV in human breast cancers: The MMTV 9.9 kb genome in breast cancer cells has been identified. The MMTV genome in human breast cancer is up to 98% identical to MMTV in mice. 2. Epidemiology: The prevalence of MMTV positive human breast cancer is about 35 to 40% of breast cancers in Western countries and 15 to 20% in China and Japan. 3. Strength of the association between MMTV and human breast cancer: Consistency—MMTV env gene sequences are consistently five-fold higher in human breast cancer as compared to benign and normal breast controls. 4. Temporality (timing) of the association: MMTV has been identified in benign and normal breast tissues up to 10 years before the development of MMTV positive breast cancer in the same patient. 5. Exposure: Exposure of humans to MMTV leads to development of MMTV positive human breast cancer. 6. Experimental evidence: MMTVs can infect human breast cells in culture; MMTV proteins are capable of malignantly transforming normal human breast epithelial cells; MMTV is a likely cause of biliary cirrhosis, which suggests a link between MMTV and the disease in humans. 7. Coherence—analogy: The life cycle and biology of MMTV in humans is almost the same as in experimental and feral mice. 8. MMTV Transmission: MMTV has been identified in human sputum and human milk. Cereals contaminated with mouse fecal material may transmit MMTV. These are potential means of transmission. 9. Biological plausibility: Retroviruses are the established cause of human cancers. Human T cell leukaemia virus type I (HTLV-1) causes adult T cell leukaemia, and human immunodeficiency virus infection (HIV) is associated with lymphoma and Kaposi sarcoma. 10. Oncogenic mechanisms: MMTV oncogenesis in humans probably differs from mice and may involve the enzyme APOBEC3B. Conclusion: In our view, the evidence is compelling that MMTV has a probable causal role in a subset of approximately 40% of human breast cancers.